Developing Specialized Vocabulary Lists for English Tourism: A Corpus-Based Approach - Wahyuningsih, Sri; Mahsar, Lalu (Journal of Language and Literature Studies, 2024)
The increasing dominance of English as the global lingua franca in tourism underscores the necessity for specialized vocabulary tailored to this sector. This study addresses a critical gap in English for Tourism (EfT) resources by developing specialized vocabulary lists using a corpus-based approach. Traditional EfT resources often fail to meet the nuanced, context-specific demands of real-world tourism communication, creating challenges for both learners and professionals. To bridge this gap, a representative corpus of tourism-related texts was compiled, and corpus analysis was conducted using three key techniques: frequency analysis, keyness analysis, and collocation analysis. These methods enabled the identification of key vocabulary and phrases relevant to various subfields within tourism, including hospitality, cultural heritage, and travel services. The identified vocabulary was subsequently categorized into thematic areas to ensure its practical applicability for tourism professionals. The study also evaluated the effectiveness of these vocabulary lists in educational contexts through pre-tests and post-tests administered to students and instructors in EfT programs. The results demonstrated a significant improvement in vocabulary proficiency, with an average 25% increase in students' performance following the intervention. These findings contribute valuable, empirically grounded resources for EfT educators, offering a practical means to enhance language proficiency and professional communication. This study highlights the importance of using authentic, context-specific materials in language education, ensuring that learners acquire the necessary skills for effective communication in tourism-related settings.